Electronic gaming machines and gambling disorder: A cross-cultural comparison between treatment-seeking subjects from Brazil and the United States. Issue 2 (15th December 2015) - Medeiros, Gustavo C.; Leppink, Eric W.; Yaemi, Ana; Mariani, Mirella; Tavares, Hermano; Grant, Jon E.
Abstract: Aims: The objective of this paper is to perform a cross-cultural comparison of gambling disorder (GD) due to electronic gaming machines (EGM), a form of gambling that may have a high addictive potential. Our goal is to investigate two treatment-seeking samples of adults collected in Brazil and the United States, countries with different socio-cultural backgrounds. This comparison may lead to a better understanding of cultural influences on GD. Methods: The total studied sample involved 733 treatment-seeking subjects: 353 men and 380 women (average age=45.80, standard deviation ±10.9). The Brazilian sample had 517 individuals and the American sample 216. Subjects were recruited by analogous strategies. Results: We found that the Brazilian sample was younger, predominantly male, less likely to be Caucasian, more likely to be partnered, tended to have a faster progression from recreational gambling to GD, and were more likely to endorse chasing losses. Conclusion: This study demonstrated that there are significant differences between treatment-seeking samples of adults presenting GD due to EGM in Brazil and in the United States. These findings suggest that cultural aspects may have a relevant role in GD due to EGM. Highlights: This study approaches gambling disorder (GD), an increasing problem but still not familiar for mental health professionals and with important research gaps. This study analyses in a standardized and comprehensive way a large sample (733 participants), recruited between 1996 and 2014. This study is the largest cross-cultural paper on GD due to EGM. We found that there are important differences between Brazil and the United States, two countries with different socio-cultural background as well as different formal legal gambling status. This research suggests the significant role of cultural factor in shaping GD. This article suggests explanations for some points related to GD that apparently depends on culture such as some demographic variables and differences in gambling behavior. This study reinforces the need for further cross-cultural research on GD. It also weakens the possibility of generalization of finding from Anglo-Saxon cultures to rest of the world.